Fractionation of palm kernel oil by short path distillation - Ramli, Muhamad Roddy (2013)
Fractionation of palm kernel oil (PKO) by short path distillation (SPD) was studied. The distillation was carried out at two feed flow rates (135 and 195 g/hr) and six temperatures, TDis (200, 210, 220, 230, 240 and 250°C). Other distillation parameters including vacuum pressure (0.001 mbar), blade rotation speed (400 rpm) and temperature of the feed material (60°C) were kept constant. Samples were collected at each experiment and analysed for product yield and physico-chemical properties including fatty acid composition (FAC), triacylglycerol (TAG) composition, slip melting point (SMP), thermal analysis by differential scanning calorimetry (DSC) and solid fat content (SFC). Crystallisation behaviour of PKO and the fractionated products were also studied by measurement of isothermal crystallisation at four temperatures, TCr (0, 5, 10 and 15°C). Crystallisation kinetics was examined by fitting the isothermal crystallisation data into the Avrami model. Fractionation of PKO by SPD resulted in an enrichment of short-chain fatty acids as well as low and some medium molecular weight TAGs in distillates. The distillates were found to have higher SMP, SFC and crystallised in sharper peaks. Melting endotherm of distillates was almost similar to that of PKO but a slight shift to lower temperatures was observed. Long-chain fatty acids and high molecular weight TAGs were concentrated in residues. The residues were lower in SMP, SFC and had broader crystallisation and melting peaks. Studies on the crystallisation behaviour by the Avrami model suggested that PKO crystallised in a plate-like crystal growth (n=2) from an instantaneous nuclei at lower crystallisation temperatures, TCr (0 and 5°C). At higher crystallisation temperatures, TCr (10 and 15°C), a plate-like (n=3) or spherulitic crystal growth (n=4) from sporadic nuclei was proposed. Fractionation of PKO altered the crystallisation behaviour of the resulted fractions. Distillates were expected to crystallise in a platelike crystal growth (n=2) from instantaneous nuclei at lower TCr. Higher TCr resulted in distillates to possibly crystallised in a rod- (n=2) and plate-like crystal growth (n=3) from sporadic nuclei. Residues were observed to possibly crystallised in a plate-like crystal growth (n=2) from an instantaneous nuclei at lower TCr. At higher TCr, it was suggested that residues crystallised in a spherulitic crystal growth (n=4) from a sporadic nuclei. PKO fractions derived by SPD were comparable to products obtained by conventional dry fractionation process. The FAC of distillates resembled closely to palm kernel stearin (PKS) and interestingly, coconut oil. Solid fat content was,however, lower than PKS. Residues were found comparable in FAC to that of palm kernel olein (PKOo). The study showed that SPD produced fractions with unique physico-chemical properties. In the crystallisation studies, the Avrami model was found to be a useful tool to predict the crystallisation behaviour of oil fractions obtained by SPD. Subsequently possible applications of the new fractions obtained could be explored.